Pemberdayaan Orang Tua dalam Stimulasi Kemampuan Membaca Kritis Anak Usia Dini di Bandung Barat - Gian Fitria Anggraini; Vivi Irzalinda; Nopiana Nopiana (FKIP UNSULTRA, 2026)
Early childhood critical reading skills need to be stimulated from an early age through the active involvement of parents in literacy activities in the family environment. However, most parents are still focused on their children's initial reading skills and lack sufficient knowledge or skills to provide critical reading stimulation. This study aims to analyze the effectiveness of parental empowerment activities in improving the ability to stimulate critical reading in early childhood in West Bandung Regency. This study used a pre-experimental design with a one-group pretest-posttest approach involving 61 parents with children aged 6–8 years. The empowerment program is carried out through the delivery of materials, joint reading practices, critical questioning exercises, the use of workbooks, and mentoring during the activity. Data were collected using pre- and post-intervention tests and analyzed descriptively and inferentially using the paired-samples t-test. The results showed that the empowerment program improved parents' knowledge and skills in providing critical reading stimulation, as evidenced by improved participants' learning outcomes after participating in the training. These findings indicate that parental empowerment is an effective strategy to strengthen the quality of family literacy through more dialogical and reflective reading interactions. This research contributes to the development of a family empowerment model to support the early development of children's critical thinking skills and can serve as an alternative partnership program between families and educational units.